Hak dan Tanggung Jawab Digital Siswa SMA dalam Penggunaan Teknologi Internet di Kota Padang - Angraini, Rita; Sapriya, Sapriya; Rahmat, Rahmat; Masyitoh, Iim Siti (Journal of Moral and Civic Education, 2025)
This paper aims to analyze the digital rights and responsibilities of students in Padang City in their use of internet technology. The rapid development of technology requires students to be not only active users, but also to understand the ethical norms, rights, and responsibilities inherent in online activities. On one hand, students have the freedom to access internet technology, but on the other, they are required to be responsible and respect the rights of others. This study is a qualitative descriptive research. The authors proposed 24 statements indicating students' digital rights and responsibilities. Data was collected through observation, interviews, and questionnaires, which were then interpreted. The results found that students understood their digital rights and responsibilities and maintained their own and others' digital privacy well. However, their academic ethics tended to be low, as students considered actions like copying material and downloading videos to be a normal practice. In terms of reporting digital rights theft and harassment, the students' awareness was quite good, but they did not know the proper procedures. Therefore, socialization is needed for relevant institutions, such as the Padang City Education Office, school supervisors, and teachers, regarding the digital rights and responsibilities of high school students in using internet technology wisely.